Electronic Structures and Optical Properties of Phenyl C71 Butyric Acid Methyl Esters. (17th December 2013) - Zhang, Cai-Rong; Han, Li-Heng; Zhe, Jian-Wu; Jin, Neng-Zhi; Shen, Yu-Lin; Yuan, Li-Hua; Wu, You-Zhi; Liu, Zi-Jiang
Abstract : Phenyl C71 butyric acid methyl ester (PC71 BM) has been adopted as electron acceptor materials in bulk heterojunction solar cells with relatively higher power conversion efficiency. The understanding of the mechanism and performance for the devices based upon PC71 BM requires the information of conformations, electronic structures, optical properties, and so forth. Here, the geometries, IR and Raman, electronic structures, polarizabilities, and hyperpolarizabilities of PC71 BM isomers are studied by using density functional theory (DFT); the absorption and excitation properties are investigated via time-dependent DFT with B3LYP, PBE0, and CAM-B3LYP functionals. The calculated results show that [6, 6]PC71 BM is more stable than [5, 6]PC71 BM due to the lower total energy. The vibrational modes of the isomers at IR and Raman peaks are quite similar. As to absorption properties, CAM-B3LYP functional is the suitable functional for describing the excitations of PC71 BM because the calculated results with CAM-B3LYP functional agree well with that of the experiment. The analysis of transition configurations and molecular orbitals demonstrated that the transitions at the absorption maxima in UV/Vis region are localized π - π * transitions in fullerenes cages. Furthermore, the larger isotropic polarizability of PC71 BM indicates that the response of PC71 BM to applied external electric field is stronger than that of PC61 BM, and therefore resulting into better nonlinear optical properties.